Case study-fujitsu and CRM : the impact of customer relationship management on Futjitsu as a service providing company - Nooren, Ella (2012)
Dissertação de mestrado em Marketing, apresentada à Faculdade de Economia da Universidade de Coimbra, sob a orientação de Arnaldo Coelho.